D'une didactique des langues à une didactique des plurilinguismes ? Réflexions pour la recherche - Dominique Montagne-Macaire (Recherches en didactique des langues et des cultures)
This talk examines some issues about plurilingualism, concerning people as well as societies, and foreign language policy at schools. This paradigm does not exist yet in the English-speaking world, but is relevant for the European area. We will try to introduce and discuss some of the often-contradictory debates centered in the domain of foreign language research. Most of the research topics concern collaborative and comparative research. Therefore, it seems to be necessary to use complementary approaches, borrowed to several different sciences and domains of research, as psycholinguistic or sociolinguistic, etc. to get a transversal overview of this emerging paradigm. This leads to "converging" and "diverging" points of view about foreign language researches. Moreover, the research topics become nowadays a priority to produce new-foreign language policy relevant knowledge. Research is of fundamental importance for the development of policies, strategies and practices in the field of plurilingualism.